The accessibility to Employment Offices in the Spainish labour market - Patricia Suárez; Matías Mayor; Bego\~na Cueto (European Regional Science Association (ERSA), 2010)
The paper uses the theoretical framework of the Spatial Economics to analyze (1) the regional unemployment disparities in Spain for males and females in three different age categories and for economic sector. We use administrative regional aggregate data to explore the distribution of the unemployed in 8109 Spanish districts (using monthly 2005-2009 data). Furthermore (2), we connect this distribution with the efficient (or inefficient) location of Employment Offices in Spain. Due to existence of asymmetric information between job seekers and firms we think that an Employment Offices increase the employment opportunities therefore reduce local unemployment. We estimate a spatial panel model in order to explain the unemployment disparities including regional fixed effect and the distance to the closest Employment Office.
Keywords: J68; J60; C21; R12; 330; Employment Offices; unemployed; accessibility